Transforming business students' dominant social paradigm: a case study of a Higher Education Institute teaching “New Economy Principles" - du Plessis, Julia (Graduate School of Business (GSB), 2019)
Over the last few decades, there has been growing recognition by governments, businesses and citizens that the current model of global economic growth is not sustainable (Fullerton, 2015). Consequently, there has been a move amongst researchers to explore alternative forms of economic systems that will allow humanity to thrive within the means of the planet. One of the biggest obstacles to realising such alternatives is the dominant social paradigm (DSP) based on an economic mindset 1950’s textbooks, which are themselves rooted in the theories of 1850 (Raworth, 2017). This DSP has led people to believe in the insatiability of human needs that can only be met by relentless economic growth, of which the negative side effects are unavoidable. This DSP has infiltrated many institutions that are responsible for the socialisation of twenty-first century future leaders - from families to higher education institutes (HEIs). In this study, I examined a private HEI whose espoused values and marketed graduate attributes claim to challenge this DSP by graduating brand professionals who seek to create meaningful, conscientious brands that take total responsibility for their actions and are purpose not profit driven. The objective of this study was to explore how successful this HEI was at instilling these values in its students so that they will behave differently in the future and to uncover what aspects of the educational experience were particularly effective/ineffective at doing so. This study took a qualitative, exploratory approach and data was collected in the form of twenty-one face to face interviews with third-year students and two email questionnaires from alumni. The findings indicated that students had an awakened consciousness and conscience with respect to reductive acts of labelling someone as “other” and this affected how they intended to behave differently towards others and in how they valued themselves. This type of consciousness paired with action is critical for the success of a new economy. This change came about primarily due to the non-discipline related subjects of Critical Studies and Creative Development, which introduced students to the concept of “othering”; the engagement with diversity, which occurred in formal ways in class and informally in a social contexts; and the institutional culture of the HEI, which celebrates the value of diversity. Where students were lacking new economy competencies was in their inability to envision humans as anything other than Homo economicus - people could be black, white, pink or purple but, particularly within the context of business, they could not be anything other than rational, calculating, self-interested beings. Students have been personally exposed to other types of diversity, but they have had little exposure to the theory or reality of Homo heuristicus, Homo reciprocans, Homo altruisticus or Homo socialis. This study therefore motivates the need for further research to explore other ways that students can be conscientised to alternative ways of being in an economic sense.